A novel approach to prevent decarburisation through electroless plating. (3rd October 2019) - Johari Teymoori, R.; Shahidi, M.; Taji, I.; Sharifalhoseini, Z.; Beidokhti, B.
ABSTRACT: Decarburisation is found as an undesirable consequence of the heat treatment cycle in hot work tool steels. In this work, an increase in the decarburisation resistance of tool steel through the electroless technique is subjected. For this purpose, the surface of the H13 tool steel was deposited by the electrodes Ni–P, Ni–B and Ni–P–B coatings. Since the carbon loss leads to a decrease in the hardness, the micro-hardness method is applied to find the influence of the mentioned coatings on the decarburisation resistance. The measurements show that all the electroless-plated steels possess higher resistance to the loss of carbon compared to the bare surface (as the reference). The results also confirmed that the incorporation of boron in the matrix of the Ni-plated layer, including Ni–B and especially Ni–P–B, prevents metal from decarburisation more effectively. The Ni–P–B coating could reduce the decarburisation depth from 0.15 to 0.035 mm.